STUDENTS’ PERCEPTIONS AND CHALLENGES IN THE USE OF SMALL GROUP DISCUSSION IN ENGLISH-SPEAKING CLASS ACTIVITIES - Cintya Rima Puspitasari; Sayit Abdul Karim; R. Yohanes Radjaban; Arifin Kurniawan (UIBU, 2023)
Small Group Discussion (SGD) is one of the techniques that can be used in learning and teaching English speaking skills. This study aims to find out students' perceptions and the challenges students encountered when using SGD in their English-speaking activities at SMK Dirgantara Putra Bangsa. This study used mixed method approaches, and the instruments used in collecting data were questionnaires and semi-structured interviews. Respondents in this study were 23 students (7 males and 16 females) from class X of SMK Dirgantara Putra Bangsa in the academic year 2023–2024and through a purposive random sampling technique. Furthermore, a questionnaire was used to figure out students' perceptions, and semi-structured interviews were conducted to find out the challenges encountered by students when using SGD. Sixrespondents (5 females and 1 male) were selected in the interview session based on their scores, they are; two students with the highest scores, two students with middle scores, and two students with low scores to be interviewed. The semi-structured interview data were analyzed qualitatively using the interactive model proposed by Miles & Huberman (1994). The results of this study show that students' perceptions of using SGD can enhance their speaking skills. Meanwhile, the results of the interviews indicated that lack of vocabulary and self-confidence were challenges those students encountered in using SGD. This learning model may help students participate, engage, and enhance their confidence in speaking English, and teachers are aware of the importance of choosing the right learning model to achieve successful learning in the classroom are a few pedagogical implications of the present study